Confiance, anthropophagie et pédagogie - Filipe Ceppas (Nantes Université, 2018)
We will evaluate the notion of trust based on an investigation of its "anthropophagic occurrences", with the intention of drawing its possible pedagogical implications. The first step is to grasp the phenomena or images that must be associated with a relationship of trust in anthropophagic rituals and in the cultures of anthropophagic societies in general. Secondly, we will question the possible consequences of this debate in the context of a supposed "crisis of Western societies" and of that of the "modern" or "classic" Subject, ending with some pedagogical ideas inspired by Oswald de Andrade's anthropophagic philosophy.